Security issues of wireless sensor networks in healthcare applications - Ng, H. S.; Sim, M. L.; Tan, C. M. (Kluwer Academic Publishers-Consultants Bureau, 2006)
The emergence of wireless sensor networks (WSNs) in healthcare applications is gaining momentum through the increasing array of wearable vital sign sensors and location tags which can track both healthcare personnel and patient status/ location continuously in real-time mode. Despite the increased range of potential application frameworks - ranging from pre-hospital, in-hospital, ambulatory and home monitoring, to long-term database collection for longitudinal trend analysis - the security gap between existing WSN designs and the requirements of medical applications remains unresolved.